2017 39th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2017
DOI: 10.1109/embc.2017.8037826
|View full text |Cite
|
Sign up to set email alerts
|

Measuring brain activation by using baseline-normalized event-related spectral perturbation in working memory task

Abstract: Understanding the cognitive function of human brain is an important step in providing scientific evidence which could help us improve the condition of memory disorders, slow down its progress or at least help the patients retain some important matters. In this study, we aimed to provide additional scientific evidence with more insight on how the brain functions at a good/bad cognitive state than the usual statistical analysis. We introduced the brain activation measurement using baseline-normalized ERSP to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In our previous study [ 14 ], we explored the differences between the attention period and the decision period in a visual cognitive experiment. We found that 85% (averaged from five participants) of ERSP data during the attention period in the alpha frequency band have a low power spectrum, whereas only 64% of ERSP data have a low power spectrum in the alpha band during the decision period.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [ 14 ], we explored the differences between the attention period and the decision period in a visual cognitive experiment. We found that 85% (averaged from five participants) of ERSP data during the attention period in the alpha frequency band have a low power spectrum, whereas only 64% of ERSP data have a low power spectrum in the alpha band during the decision period.…”
Section: Introductionmentioning
confidence: 99%